2018
DOI: 10.1101/424812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life in Children and Adolescents with Osteogenesis Imperfecta: cross-sectional study

Abstract: Background: Osteogenesis imperfecta (OI) affects dental and craniofacial development and may therefore impair Oral Health-Related Quality of Life (OHRQoL). However, little is known about OHRQoL in children and adolescents with OI. The aim of this study was to explore the influence of OI severity on oral health-related quality of life in children and adolescents.Methods: Children and adolescents aged 8-14 years were recruited in the context of a multicenter longitudinal study (Brittle Bone Disease Consortium) t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Tosi et al () reported health issues encountered by adults with OI throughout their lifespan. For instance, about 50% of individuals with OI are born with dentinogenesis imperfecta (Biria, Abbas, Mozaffar, & Ahmadi, ), which affects the quality of life of children, adolescents, and adults (Najirad et al, ). Second, the present review excluded case reports on skeletal manifestations because it was addressed by the OI community (Forlino et al, ; Forlino & Marini, ; Rauch & Glorieux, ), and rather focused on the extra skeletal manifestations of OI due to paucity of research.…”
Section: Discussionmentioning
confidence: 99%
“…Tosi et al () reported health issues encountered by adults with OI throughout their lifespan. For instance, about 50% of individuals with OI are born with dentinogenesis imperfecta (Biria, Abbas, Mozaffar, & Ahmadi, ), which affects the quality of life of children, adolescents, and adults (Najirad et al, ). Second, the present review excluded case reports on skeletal manifestations because it was addressed by the OI community (Forlino et al, ; Forlino & Marini, ; Rauch & Glorieux, ), and rather focused on the extra skeletal manifestations of OI due to paucity of research.…”
Section: Discussionmentioning
confidence: 99%
“…The latter seems to be related to vertically small jaws and consequent anterior growth rotation of the lower jaw [10]. The quality of life of patients with OI may be impaired by aesthetic and, especially, functional concerns related to both DI and malocclusions, typically reverse overjet, posterior crossbite and open bite [12,13]. The aetiological sequences behind these occlusal features are only partly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Dental problems such as dentinogenesis imperfecta (DI), agenesis, impacted teeth, and ectopic eruption contribute to malocclusion in this population [10,11]. These anomalies that develop in early life and worsen with age in the OI population can lead to difficulties chewing, biting, and speaking and can cause pain and discomfort [12].…”
Section: Introductionmentioning
confidence: 99%